Scanning electron microscopy of Onchocerca fasciata (Filarioidea: Onchocercidae) adults, microfilariae and eggs with notes on histopathological findings in camels - Ghahvei, Younes (Parasit Vectors, 2020)
BACKGROUND: Onchocerca fasciata is a prevalent filarial species in camelids of Asia and Africa forming nodules in the skin of dromedary and Bactrian camels. In spite of recent advances in the biology and epidemiology of this nematode species, a relatively scant number of studies have focussed on the morphology of this parasite. The main objective of this study was to describe morphological characteristics of adults, microfilariae and eggs of O. fasciata by scanning electron microscopy (SEM), staining and histology. METHODS: From April 2016 to March 2017 dromedary camels (n = 456) were inspected for infection with O. fasciata in a slaughterhouse in Kerman (south of Iran). Adult worms in nodules were isolated by digestion of nodules in collagenase and used for SEM. Skin nodules were also fixed, sectioned and stained with hematoxylin and eosin for histopathology. Skin microfilariae that were isolated from tissues surrounding the nodules were confirmed as O. fasciata by sequencing of the cytochrome c oxidase subunit 1 (cox1) and 12S rRNA genes and used for SEM and Giemsa staining. RESULTS: Single or multiple O. fasciata nodules (1.2–2.2 cm in diameter and 507–845 mg in weight) were found in 30.3% of the examined camels. SEM analysis helped identify 18 papillae in the caudal region of the male. Discontinuous longitudinal cuticular crests were observed in the posterior region of the male. In female nematodes, the ridges had a rounded shape with a height/width ratio of 7/16 in longitudinal sections. Unsheathed skin microfilariae with a rounded anterior extremity measured 210.7 × 2.5 μm on average. Developed eggs containing microfilariae measured 35.9 × 31.0 μm and their smooth shell surface had characteristic tongue-like appendages. In addition to inflammatory reactions surrounding the parasites, accumulation of intracellular ceroid pigment, golden-yellow to brown in colour, was observed within macrophages upon histopathological examination. CONCLUSIONS: We found longitudinal crests on the surface of the posterior region of the male nematode. Measurements of the main morphological features of microfilariae and eggs, and the shape index of ridges (height/width) in female nematodes are described for the first time. [Image: see text]